Relacionamentos interpessoais e autoimagem de pessoas idosas institucionalizadas e não institucionalizadas - Duarte, Milena Pinheiro (2024)
Demographic changes show an increase in the number of people over the age of 60, making it a concern to ensure that this ageing takes place successfully. For this to happen, care is needed in biopsychosocial aspects that can affect the quality of this ageing, such as interpersonal relationships and self-image. Care can be given to families or to long-term care facilities for the elderly. Because both contexts are crossed by social stereotypes and each person experiences the same situation differently, the aim was to assess the self-image and interpersonal relationship perceptions of institutionalized and non-institutionalized elderly people. To this end, a qualitative multiple case study was carried out. Six elderly people took part in the study, three institutionalized and three non-institutionalized, aged between 65 and 84. The instruments used were a sociodemographic questionnaire, Mini Mental State Examination, World Health Organization Quality of Life - Bref instrument, semi-structured interview, Zulliger Test using the Comprehensive System and the Apperception Technique for the Elderly. Data was collected in two individual sessions of approximately 60 minutes each. For data analysis, a methodological triangulation was carried out, encompassing the findings of the instruments. The results showed that non-institutionalized elderly people can be influenced by social expectations and externalize more positive narratives about aspects of ageing, even though they have internal vulnerabilities that affect their daily functioning. Institutionalized elderly people, on the other hand, are able to highlight their singularities more easily, which may be due to a self-affirming stance towards the environment in which they live. Among the results, it stands out that both institutionalized and non-institutionalized elderly people showed affective, interpersonal and self-image weaknesses. The use of instruments of different natures proved to be an important methodological tool, as it enabled a more complete understanding of the elderly person's personality dynamics, providing information that helped to investigate aspects of self-image and interpersonal relationships. It is concluded that the study met its objectives, enabling an understanding of interpersonal relationships and self-image in both contexts, helping to provide visibility for the elderly and their demands.